IMPROVING THE ROLE OF MEDICAL NURSES IN THE STUDY, TREATMENT AND PREVENTION OF DIGESTIVE DISEASES - Eshbaeva, K.U.; Rustamova, X.E.; Stojarova, N.K.; Abdurashidova, Sh.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
One of the most common diseases of the population in many countries are diseases of the digestive system. In Uzbekistan, diseases of the digestive system (BOP) occupy the third ranking place in the structure of the causes of the general and primary morbidity of the population. The participation of nurses in the treatment of prophylaxis and the study of the needs of patients with eating disorders and diseases of the gastrointestinal tract has a very high theoretical, theoretical spectrum and practical application, the result of which will be not only an increase in the quality of medical care for the population, improvement of nursing practice, but also an increase in the role of the nursing profession in the fight against noncommunicable diseases .